ANALISIS IMPLEMENTASI PROGRAM PELAYANAN KELUARGA BERENCANA (KB) DI KANTOR DPPKB KOTA PEMATANGSIANTAR - Vera A. Pasaribu; Tiarma Widia Devi Sitanggang; Alfred N. Tambunan; Agus Kristin Saruksuk; Vera Aginta Purba (Jurnal Ilmu Sosial Dan Politik, 2022)
The purpose of this study was to analyze the Implementation of the Family Planning Service Program (KB) at DPPKB Pematangsiantar City through a qualitative descriptive approach. The data used are primary data and secondary data. Primary data was obtained through interviews conducted with key informants, namely the Head of DPPKB Staffing, the main informant, namely the Secretary and Head of the DPPKB Prosperous Family and additional informants, namely five community members participating in family planning. Secondary data obtained through documentation from the research location. The data analysis technique used in this research is based on John Creswell's theory where there are six steps of data analysis namely, managing data, reading all data, analyzing data by coding data, coding process, describing data, and interpreting data. The results of the study show that the implementation of the Family Planning Service Program in Pematangsiantar City is good enough, which is supported by the existence of Standards, goals, policy objectives, Resources, Communication, Commitment, Bureaucratic Structure, and Implementor Dispositions. To achieve the objectives of the family planning program, it is suggested that the DPPKB should further improve the quality of its services, increase the number of implementers, improve communication and improve coordination between implementers and the community planning participants, as well as the local community in order to further increase maximum participation in the family planning program in Pematangsiantar City.